Safety and immunogenicity of an indigenously developed tetanus toxoid, diphtheria toxoid, and acellular pertussis vaccine (Tdap) in adults, adolescents, and children in India. (31st December 2023) - Sharma, Hitt J; Parekh, Sameer; Pujari, Pramod; Shewale, Sunil; Desai, Shivani; Kawade, Anand; Ravi, Mandyam; Oswal, Jitendra; James, Saji; Mahantashetti, N.; Munshi, Renuka; Ghosh, Apurba; et al.
ABSTRACT: Background: This study assessed safety and immunogenicity of Serum Institute of India Pvt Ltd (SIIPL)'s tetanus toxoid (TT), diphtheria toxoid (DT), and acellular pertussis booster vaccine (Tdap). Research Design and Methods: In this Phase II/III, multicenter, randomized, active-controlled, open-label study, 1500 healthy individuals, aged 4–65 years, were randomized to receive a single dose of SIIPL Tdap or comparator Tdap vaccine (Boostrix®; GlaxoSmithKlines, India). Adverse events (AEs) during initial 30 minutes, 7-day, 30-day post-vaccination were assessed. Blood samples were taken before and 30 days post-vaccination for immunogenicity assessment. Results: No significant differences in incidence of local and systemic solicited AEs were observed between the two groups; no vaccine-related serious AEs were reported. SIIPL Tdap was non-inferior to comparator Tdap in achieving booster responses to TT and DT in 75.2% and 70.8% of the participants, respectively, and to pertussis toxoid (PT), pertactin (PRN), and filamentous hemagglutinin (FHA) in 94.3%, 92.6%, and 95.0% of the participants, respectively. Anti-PT, anti-PRN, and anti-FHA antibody geometric mean titers in both the groups, were significantly higher post-vaccination compared to pre-vaccination. Conclusions: Booster vaccination with SIIPL Tdap was non-inferior to comparator Tdap with respect to immunogenicity against tetanus, diphtheria, and pertussis and was well tolerated.